Pola Pengeluaran Penerima Beasiswa KIP KULIAH: Prioritas Penggunaan Dana Antara Kebutuhan Esensial dan Gaya Hidup - Aghnia Ilmi Diniyati; Gina Fadillah; Livia Anggina; Raka Prasetya; Salwa Salsabila; Surani Erni Morowati; Rama Wijaya Abdul Rozak (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The KIP college scholarship is one of the government programs to help outstanding students but with poor economic backgrounds. The use of KIP college funds should be used for educational needs as it should be that the money comes from the government. The purpose of this study is to analyze the spending patterns of KIP college recipients between essential needs and lifestyle needs. The method used in this research is quantitative method. In this study used data collection in the form of a closed questionnaire through google form, this questionnaire has been filled in by 103 KIP college student respondents spread from public universities in Indonesia. The results showed that the KIP college scholarship had helped the recipients of the scholarship to meet the costs of living and education, they also had a positive impact on the responsibility and wisdom of the pattern of spending funds that had been given by the government as evidenced by the priority scale of supporting lectures, but there were still some respondents who used KIP college funds to meet lifestyle.